Close ba tayo? communication choices by members of Singles for Christ West C5 - Manila - Badilla, Maria Criselda G. Gatchalian (2009.)
"This master's thesis determines the role of New Communication Technologies (NCt) (i.e., cellphone voice calls, text messaging, email and instant messaging) as communication channels in building and maintaining intimate relations among Singles for Christ members of West C5. To ascertain the influence of sex, hierarchy, message content and media characteristics, the study employed six pairs or research collaborators through participatory collaborative inquiry, dyadic interviews and focus group discussion. Using concepts from Ball-Rokeach and De Fleur's Uses and Gratifications and Dependency Model, Altman and Taylor's Social Penetration Theory, Daft and Lengel's Media Richness Theory and Rogers and Kincaid's, the data were analyzed and revealed that NCT-mediated communication had an impact on enriching personal relationships within SFC West C5. A certain dependency on NCT revolutionized the way members communicate with each other. This dependency on NCt enabled them to be constantly in touch with other members, though the quantity of interactions may have increased but it is lacking in quality. Self-disclosure was found to be best expressed through their regular face to face household meetings. NCT can enhance the development and maintenance of relationships within SFC West C5, but because its quality and depth are limited, relationships are still better developed and maintained through face to face communication."
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Vita.
Keywords: Communication -- Religious Aspects -- Catholic Church -- Manila Metropolitan Area; Cellular telephones -- Religious aspects -- Catholic Church -- Mania Metropolitan Area; Information technology -- Religious aspects -- Catholic Church -- Manila Metropolitan Area